THE ROLE OF THE YOUNG MUSLIM GENERATION IN INTERNATIONAL DIPLOMACY: A CASE STUDY OF THE GERAKAN PEMUDA ANSOR IN INDONESIA - Ahmad Khotib Lubis (Yayasan Dinamika Literasi Jambi, 2025)
International diplomacy plays a very important role in shaping the image of moderate Islam on the global stage, and GP Ansor, as a Muslim youth organization in Indonesia, has played an active role in this effort. Through various diplomatic strategies, such as narrative diplomacy using social media and digital platforms, GP Ansor has succeeded in conveying the message of peaceful, tolerant, and inclusive Islam to international audiences. The organization is also active in international forums such as peace conferences and interfaith dialogues, trying to change the negative perception of Islam that is often associated with extremism and conflict. However, major challenges arise from GP Ansor's limited access to formal diplomacy dominated by countries and international institutions, as well as global perceptions that often simplify the face of Islam. In addition, differences in ideology and global political interests also complicate international cooperation based on Islamic moderation. Limited human and financial resources are also significant obstacles to achieving consistent and professional international diplomacy.